Hair regrowth and maintenance in alopecia universalis patient treated with nonablative Er:YAG laser. Issue 11 (12th November 2021) - McCarthy, Madison; Day, Doris; Talaber, Iva
Abstract: Hair regrowth with no adverse effects following nonablative 2940‐nm Er:YAG laser treatment in alopecia universalis patient resulted in high patient satisfaction and compliance. As the main challenge in alopecia universalis is maintenance of regrown hair, patient compliance associated with this treatment might represent an advantage over traditional treatment modalities. Abstract : Hair regrowth with no adverse effects following nonablative 2940‐nm Er:YAG laser treatment in alopecia universalis patient resulted in high patient satisfaction and compliance. As the main challenge in alopecia universalis is maintenance of regrown hair, patient compliance associated with this treatment might represent an advantage over traditional treatment modalities.